Organization and Operation Principles of Cooperative Groups in Vietnam - Duy, Nguyen Dang; Hung, Nguyen Vinh (Journal of Posthumanism, 2025)
Nowadays, Decree No. 77/2019/ND-CP regulating cooperative groups has been applied and implemented for a relatively long time in Vietnam. However, from the actual organization and operation of the collaborative group, the provisions of Decree No. 77/2019/ND-CP still exist many limitations, shortcomings, and not reasonable. Therefore, the article studies the principles of organization and operation of the cooperative group under the current law in Vietnam to points out the weaknesses, shortcomings and proposes some recommendations to improve operational efficiency for this important collective economic model. Additionally, the law completion of the cooperative groups model also contributes to the attraction of the attention of investors before the background that Vietnam is an advantageous business investment environment.